Futures Challenges in Thyroid Hormone Signaling Research - Flamant, Frédéric (Frontiers in Endocrinology, 2016)
The canonical pathway of thyroid hormone signaling involves its binding to nuclear receptors (TRs) acting directly on the transcription of a number of genes. Recent genome wide studies revealed that chromatin occupancy by TR is not sufficient for transactivation of gene expression. Reciprocally, in some cases, DNA binding by TR may not be required for cellular response. This leaves many new questions to be addressed in future research.